Development of a microstructured tissue phantom with adaptable optical properties for use with microscopes and fluorescence lifetime imaging systems. Issue 7 (26th June 2022) - Freymüller, Christian; Ströbl, Stephan; Aumiller, Maximilian; Eisel, Maximilian; Sroka, Ronald; Rühm, Adrian
Abstract: Objectives: For the development and validation of diagnostic procedures based on microscopic methods, knowledge about the imaging depth and achievable resolution in tissue is crucial. This poses the challenge to develop a microscopic artificial phantom focused on the microscopic instead of the macroscopic optical tissue characteristics. Methods: As existing artificial tissue phantoms designed for image forming systems are primarily targeted at wide field applications, they are unsuited for reaching the formulated objective. Therefore, a microscopy‐ and microendoscopy‐suited artificial tissue phantom was developed and characterized. It is based on a microstructured glass surface coated with fluorescent beads at known depths covered by a scattering agent with modifiable optical properties. The phantom was examined with different kinds of microscopy systems in order to characterize its quality and stability and to demonstrate its usefulness for instrument comparison, for example, regarding structural as well as fluorescence lifetime analysis. Results: The analysis of the manufactured microstructured glass surfaces showed high regularity in their physical dimensions in accordance with the specifications. Measurements of the optical parameters of the scattering medium were consistent with simulations. The fluorescent beads coating proved to be stable for a respectable period of time (about a week). The developed artificial tissue phantom was successfully used to detect differences in image quality between a research microscope and an endoscopy based system. Plausible causes for the observed differences could be derived based on the well known microstructure of the phantom. Conclusions: The artificial tissue phantom is well suited for the intended use with microscopic and microendoscopic systems. Due to its configurable design, it can be adapted to a wide range of applications. It is especially targeted at the characterization and calibration of clinical imaging systems that often lack extensive positioning capabilities such as an intrinsic z ‐stage.